The material consequences of welfare states: Benefit generosity and absolute poverty in 16 OECD countries - Lyle Scruggs; James P. Allan (Luxembourg Income Study (LIS), 2005)
Several recent studies have focused attention on the relationship between welfare states and poverty. This work has looked primarily at relative poverty, employing concepts of welfare state generosity that are problematic. This has made it difficult to evaluate claims that equality has come at the expense of economic growth. In this paper we examine more directly the relationship between welfare state generosity in three social insurance programs - unemployment, sickness and pensions - and poverty levels in advanced industrial democracies in the last quarter of the twentieth century. Our results strongly suggest that more generous entitlements to key social insurance programs are associated not only with lower relative poverty, but also lower absolute poverty. This supports the contention that promoting relative economic equality can improve the absolute material well-being of the poor. However, we find no evidence to suggest that relatively more generous unemployment benefits systematically reduce poverty.
Keywords: 330; Armut; Sozialstaat; OECD-Staaten